PENGARUH PENERAPAN ETIKA BISNIS DI CV. INDONESIA MOBILE SYSTEM (M-PULSA) TERHADAP KARYAWAN DAN PELANGGAN - Goldyn Alaraaf, Feris; Kuswardijah, Sugi; Harjanti, Wulandari (Ekomania, 2023)
Implementing ethical behavior in daily activities is a moral act of a positive person. It is not merely applied for individual, but it can be used and applied to companies that needed to grow and survive consistently. Ethics in business create comfort not only for customers as consumer of the goods and services provided, but comfort is also felt by all parts of the workers involved in a company. Once all workers are comfortable at work, customers’ services will improve automatically as well. In a company that runs a business, customers are determinants whether a company is able to survive and continue to thrive in the midst of fierce business competition or not. For companies, customer service is an important point in the process of creating an impression to consumers or providing a close bond with consumers to be loyal to the products offered. This study was conducted in CV. Indonesia Mobile System where this company made a system of order behave the scope of the company which impacted on improving services to consumers and affects to all people who were using the company’s products. This study aimed to find out the success of CV. Indonesia Mobile System which has created a customer service ethics system and obtained the consumers’ and employee level of satisfaction in cooperate. This research used a descriptive research method with a qualitative approach, a method that collected data by interacting directly with respondents